Kinase Function of Brassinosteroid Receptor Specified by Two Allosterically Regulated Subdomains - Ali, Khawar; Li, Wenjuan; Qin, Yaopeng; Wang, Shanshan; Feng, Lijie; Wei, Qiang; Bai, Qunwei; Zheng, Bowen; Li, Guishuang; Ren, Hongyan; Wu, Guang (Frontiers in Plant Science, 2022)
Plants acquire the ability to adapt to the environment using transmembrane receptor-like kinases (RLKs) to sense the challenges from their surroundings and respond appropriately. RLKs perceive a variety of ligands through their variable extracellular domains (ECDs) that activate the highly conserved intracellular kinase domains (KDs) to control distinct biological functions through a well-developed downstream signaling cascade. A new study has emerged that brassinosteroid insensitive 1 (BRI1) family and excess microsporocytes1 (EMS1) but not GASSHO1 (GSO1) and other RLKs control distinct biological functions through the same signaling pathway, raising a question how the signaling pathway represented by BRI1 is specified. Here we confirm that BRI1-KD is not functionally replaceable by GSO1-KD since the chimeric BRI1-GSO1 cannot rescue bri1 mutants. We then identify two sub-domains S1 and S2. BRI1 with its S1 and S2 substituted by that of GSO1 cannot rescue bri1 mutants. Conversely, chimeric BRI1-GSO1 with its S1 and S2 substituted by that of BRI1 can rescue bri1 mutants, suggesting that S1 and S2 are the sufficient requirements to specify the signaling function of BRI1. Consequently, all the other sub-domains in the KD of BRI1 are functionally replaceable by that of GSO1 although the in vitro kinase activities vary after replacements, suggesting their functional robustness and mutational plasticity with diverse kinase activity. Interestingly, S1 contains αC-β4 loop as an allosteric hotspot and S2 includes kinase activation loop, proposedly regulating kinase activities. Further analysis reveals that this specific function requires β4 and β5 in addition to αC-β4 loop in S1. We, therefore, suggest that BRI1 specifies its kinase function through an allosteric regulation of these two sub-domains to control its distinct biological functions, providing a new insight into the kinase evolution.